Neuromuscular profile of Handball players during a short-term condensed competition in Brazil - Lima, Leonardo Coelho Rabello [UNESP]; Teixeira, Inaian Pignatti [UNESP]; Nakamura, Priscila Missaki [UNESP]; Hayakawa, Marina Yumi [UNESP]; Assumpção, Claudio Oliveira [UNESP]; Menzes, Rafael Pombo (Universidade Federal de Santa Catarina, 2015)
The aim of this study was to assess the neuromuscular profile of handball (TH) players during a short-term condensed competition. Nine TH athletes (age: 23 ± 3 years; height: 176.2 ± 10.5 cm; mass: 75.3 ± 8.6 kg) played 5 handball matches in 5 consecutive days and had exercise-induced muscle damage (EIMD) markers such as soreness (SOR), thigh circumference (CIR), knee range of motion (ROM) and countermovement jump height (CMJ) collected before the first match and at the end of each day of competition. Changes over time in these markers were analyzed. Significant changes were found for all EIMD markers assessed. CMJ significantly decreased at the fourth day of competition when compared to baseline (0.41 ± 0.03 m vs. 0.45 ± 0.02 m). ROM decreased on the first day of competition and remained stable until the last day of competition (baseline: 126.5 ± 7.2º; 1st day: 115.8 ± 5.9º; 2nd day: 115 ± 7º; 3rd day: 113.9 ± 8.8º; 4th day: 114.4 ± 8.6º). SOR and CIR were increased at the second day of competition and remained altered thereafter. It was concluded that the characteristics of short-term condensed competition have led TH athletes to significant EIMD. If not avoided, EIMD might lead to reductions in performance in the most important (final) matches.

O objetivo do presente estudo foi medir o perfil neuromuscular de jogadores de handebol durante uma competição em formato de jogos. Nove jogadores de handebol (idade: 23 ± 3 anos; estatura: 176,2 ± 10,5 cm; massa: 75,3 ± 8,6 kg) jogaram cinco partidas da modalidade em cinco dias consecutivos e tiveram marcadores de DM [como percepção subjetiva de dor (PSD), circunferência da coxa (CIR), amplitude de movimento do joelho (ADM) e altura de salto com contra-movimento (AS)] coletados antes da primeira partida e ao final de cada dia de competição. Mudanças ao longo do tempo nesses marcadores foram analisadas. Alterações significantes foram encontradas para todos os marcadores de DM coletados. A AS diminuiu significantemente durante o quarto dia de competição, quando comparado ao valor basal (0,41 ± 0,03 m vs. 0,45 ± 0,02 m). A ADM diminuiu após o primeiro dia de competição e permaneceu comprometida até o último dia (basal: 126,5 ± 7,2º; 1o dia: 115,8 ± 5,9º; 2o dia: 115 ± 7º; 3odia: 113,9 ± 8,8º; 4o dia: 114,4 ± 8,6º). A PSD e a CIR apresentaram aumento durante o segundo dia de competição e permaneceram alteradas até o final da mesma. Concluímos que a característica condensada das competições de handebol no Brasil leva a um quadro de DM significante. Se não evitado, o DM pode levar a comprometimentos no desempenho nas partidas mais importantes da competição (finais).
Perfil neuromuscular de atletas de handebol durante curta competição no Brasil
Keywords: Fatigue; Neuromuscular monitoring; Sports; Wounds and Injuries; Esportes; Fadiga; Ferimentos e Lesões; Monitoração neuromuscular